Imaging Manifestations of Intrahepatic Reactive Lymphoid Hyperplasia: A Case Report and Literature Review - Zhang, Bingqian; Zou, Mingyue; Lu, Zengxin; Mao, Haijia; Huang, Ya’nan; Liu, Fang; Zhao, Zhenhua (Frontiers in Oncology, 2021)
Reactive lymphoid hyperplasia (RLH) of the liver is an uncommon benign lesion. It is usually difficult to differentiate from hepatocellular carcinoma (HCC) and liver metastases in imaging, and it is difficult to differentiate from lymphoma in pathology. On account of its rarity and controversial issues, we report a case report and review the literature to discuss its clinical, imaging and pathological manifestations, which will be helpful to improve the clinical decision-making.